Análise comparativa entre sistemas fotovoltaicos multifuncionais de único e duplo estágios de conversão de energia - Silveira, Rafaela Dizaró (2019)
This work presents the study, implementation and comparative analysis involving four topologies of multifunctional photovoltaic (M-PV) systems. The M-PV systems, which include both single- and double- stage energy conversion, are connected to three-phase four-wire electrical systems. The M-PV systems are designed to perform the following functionalities: 1) maximum power tracking in PV arrays; 2) injection of active power into the grid and 3) active power-line conditioning including compensation of load reactive power, unbalances, as well as suppressing of load harmonic currents. Therefore, besides the basic functions of conventional PV systems, the M-PV systems discussed in this work also contribute to power quality indicators improvement. Four topologies of PV systems are studied in this work by using three single-phase full-bridge (1-FB) grid-connected inverters. The first, named SFVM-1E-C, involves a single stage of energy conversion. It is implemented using three 1-FB inverters connected to a common DC-bus voltage. The second, called SFVM-2E-C, is implemented incorporating a step-up DC-DC converter (Boost converter) in the SFVM-1E-C topology. The third topology, called SFVM-1E-I, also makes use of three grid-tied 1-FB inverters; however, each one of them is connected to an independent DC-bus voltage. Finally, in the topology named SFVM-2E-I, three Boost converters are incorporated to the SFVM-1E-I topology. All topologies employ independent control strategies, meaning that the three-phase four-wire system can be treated as three single-phase systems, such that the current of each phase can be controlled individually. In order to guarantee the extraction of the maximum power from the PV arrays, Perturb and Observe (P&O) maximum power point tracking (MPPT) technique is employed. In this work, simulation results and experimental tests are presented to evaluate the static and dynamic performances of the M-PV topologies. Comparative analyses are performed to determine the advantages, limitations and applicability involving each studied topology.